Desynchronized Functional Activities Between Brain White and Gray Matter in Major Depression Disorder - Zhang, Yuqun; Kong, Youyong; Liu, Xiaoyun; Gao, Heren; Yin, Yingying; Hou, Zhenghua; Zhang, Haisan; Zhang, Hongxing; Xie, Chunming; Zhang, Zhijun; Yuan, Yonggui (Journal of magnetic resonance imaging, 2021)
Background Alterations in gray matter (GM) have been recognized as playing an important role in the neurobiological mechanism underlying major depressive disorder (MDD) and antidepressant responses. However, little is known about white matter (WM) connectivity in MDD, leaving an incomplete understanding of the pathophysiology of the disorder. Purpose To examine the functional connectivity (FC) of WM, GM, and WM‐GM in MDD patients and explore the relationship between FC and antidepressant response. Study Type Longitudinal study. Subjects In all, 129 MDD patients and 89 healthy controls (HC). Field Strength/Sequence Whole‐brain blood oxygen level‐dependent (BOLD) single‐shot echo planar imaging was acquired at 3.0T. Assessment At baseline, all participants received Hamilton depression rating scale (HAMD) assessment and an fMRI scan. After 2‐ and 8‐week antidepressant treatment, patients completed the HAMD again. The HAMD reductive rate of 2‐ and 8‐weeks were calculated. Statistical Tests The comparisons of age, education, HAMD scores, and FC values (false discovery rate correction) between patients and controls were calculated with a two‐sample t‐test. The chi‐square test was employed to compare the differences of gender between these two groups. Correlations between FC and HAMD, as well as the reductive rate of HAMD, were analyzed with Pearson or Spearman correlation. Receiver operator curve analysis was performed to predict the antidepressant response. Results Compared to HC, MDD patients exhibited widespread decreases in FC of WM‐GM. Furthermore, 28 GM regions and 11 WM bundles had lower connectivity in MDD patients. At baseline, four FC of WM‐GM showed negative correlations with the HAMD scores. Six FC of WM‐GM correlated with the 2‐week reductive rate of HAMD. Moreover, FC in GM, WM, and WM‐GM also exhibited significantly positive correlations with an 8‐week reductive rate of HAMD. Data Conclusion The FC of WM‐GM was decreased in MDD and may play a role in its pathophysiology and antidepressant responses. Level of Evidence 2. Technical Efficacy Stage 2.